Natural Antioxidant and Anticarcinogenic Compounds from Two Varieties of Iranian Garlic - Ramezani Kharazi, Parvin; Peyvast, Gholamali (Asian Journal of Chemistry, 2016)
Conjugated linoleic acid (CLA) or its downstream metabolites are screened for its various antioxidant and antitumour actvities in two varieties of Iranian garlic [Allium sativum, var. sativum (I) and Allium ampeloprasum, var. holmens (II)] that are cultivated in north of Iran. In this work, IR, GC and GC-mass have been used for the characterization of unsaturated fatty acid methyl ester (UFAMEs). The qualitative and quantitative analysis of garlic extract showed significant amount of 9,12-octadecadienoic acid methyl ester and 11,14-eicosadienoic acid methyl ester among other UFAMEs for (II).